2013
DOI: 10.1186/1476-4598-12-30
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-32 (miR-32) regulates phosphatase and tensin homologue (PTEN) expression and promotes growth, migration, and invasion in colorectal carcinoma cells

Abstract: BackgroundColorectal carcinoma (CRC) is one of the leading causes of cancer-related mortality worldwide. MicroRNAs (miRNAs, miRs) play important roles in carcinogenesis. MiR-32 has been shown to be upregulated in CRC. In this study, we identified the potential effects of miR-32 on some important biological properties of CRC cells, and clarified the regulation of PTEN by miR-32.MethodsThe effect of miR-32 on PTEN expression was assessed in CRC cell lines with miR-32 mimics/inhibitor to increase/decrease miR-32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 37 publications
5
138
1
2
Order By: Relevance
“…PTEN functions as a negative regulator of the phosphoinositide 3-kinase/Akt pathway through dephosphorylation of phosphatidylinositol 3,4,5 trisphosphate, and is involved in regulation of cellular proliferation, metastasis and apoptosis during progression of cancers (34). PTEN has been reported to be regulated by numerous miRNAs in multiple cancers, including colorectal carcinoma, glioma, ovarian and breast cancer (29,(35)(36)(37). In the present study, it was also determined that miR-20b inhibited PTEN expression by directly binding to the mRNA 3'-UTR of PTEN in VCaP and PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN functions as a negative regulator of the phosphoinositide 3-kinase/Akt pathway through dephosphorylation of phosphatidylinositol 3,4,5 trisphosphate, and is involved in regulation of cellular proliferation, metastasis and apoptosis during progression of cancers (34). PTEN has been reported to be regulated by numerous miRNAs in multiple cancers, including colorectal carcinoma, glioma, ovarian and breast cancer (29,(35)(36)(37). In the present study, it was also determined that miR-20b inhibited PTEN expression by directly binding to the mRNA 3'-UTR of PTEN in VCaP and PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-375 is associated with drug resistance in ovarian (71) and cervical cancer (72). Although no study has reported the role of miR-32 and -217 in drug resistance, it is associated with drug resistance-related processes such as cell proliferation, invasion and migration (73)(74)(75). Collectively, among the 7 microRNAs most strongly targeting HNF1B, the majority were involved in drug resistance in ovarian and other types of cancers, suggesting that the gene also mediates drug resistance.…”
Section: Microrna-mrna Interaction Analysis Indicating the Associatiomentioning
confidence: 99%
“…A complicated metabolic disorder such as diabetes is affected by broad gene expression in numerous tissues. A recent study has reported that six candidate genes were found significantly high in the T2DM study; ENND1B, LYN, MRPL30, POC1B, PRKCB, and RP4-655J12.3 [28]. PRKCB is observed to be upregulated in skeletal muscle, islets, adipose tissue, and blood, and downregulated in the liver of T2DM subject, suggested to involve in IR and decreased β-cell function.…”
Section: Gene Expression In T2dmmentioning
confidence: 99%
“…It is a complex endocrine and metabolic disorder with various of complications rises, characterized by IR and deficient β-cell function [28]. The pathogenesis of the disease is suggested to be affected by the intercommunication of multiple genetics and risk factors.…”
Section: Gene Expression In T2dmmentioning
confidence: 99%
See 1 more Smart Citation